2008
DOI: 10.1186/ar2354
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of antidiabetic thiazolidinediones prevents bone resorption rather than cartilage changes in experimental polyarthritis

Abstract: Background Rosiglitazone and pioglitazone are high-affinity peroxisome proliferator-activated receptor (PPAR)-γ agonists with potent anti-diabetic properties and potential antiinflammatory effects. We compared the ability of a range of oral doses of these thiazolidinediones, including those sufficient to restore insulin sensitization, to inhibit the pathogenesis of adjuvant-induced arthritis (AIA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
12

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 71 publications
5
48
1
12
Order By: Relevance
“…We used Rosiglitazone as an anti-inflammatory drug because it is a peroxisome proliferator-activated receptor-gamma (PPAR-γ) agonist which has anti-diabetic properties and potential anti-inflammatory effects as recent studies have shown (Sańchez-Hidalgo et al, 2005;Koufany et al, 2008). Currently, Kolak and her collogues have reported that chronic Rosiglitazone therapy altered gene expression involved in fatty acid synthesis and inflammation (Kolak et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We used Rosiglitazone as an anti-inflammatory drug because it is a peroxisome proliferator-activated receptor-gamma (PPAR-γ) agonist which has anti-diabetic properties and potential anti-inflammatory effects as recent studies have shown (Sańchez-Hidalgo et al, 2005;Koufany et al, 2008). Currently, Kolak and her collogues have reported that chronic Rosiglitazone therapy altered gene expression involved in fatty acid synthesis and inflammation (Kolak et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Statins (HMG CoA reductases) have been shown to reduce cardiovascular events and mortality. Statin treatment resulted in a significant reduction of plasma resistin in patients with type 2 diabetes and also downregulated mRNA resistin levels in PBMCs [40,136].…”
Section: Resistin As a Potential Pharmacological Targetmentioning
confidence: 98%
“…Moreover, it has been recently shown that higher doses of TZDs reduced bone erosions and prevented inflammatory bone loss in an experimental model of autoimmune arthritis [136].…”
Section: Resistin As a Potential Pharmacological Targetmentioning
confidence: 99%
“…Previously, it was demonstrated that rosiglitazone reduced lung inflammation in a rat model of endotoxemia induced by lipopolysaccharide [4]. Furthermore, rosiglitazone decreased neutrophil influx, pro-inflammatory cytokines, chemokines, and adhesion molecule levels in inflammation models in both rats and mice [5][6][7].…”
Section: Introductionmentioning
confidence: 96%